Efisiensi Kinerja Rantai Pasok Kopi Robusta Di Kabupaten Kubu Raya - Aswat, Jumaratul; Maswadi, Maswadi; Kusrini, Novira (Politeknik Negeri Lampung., 2023)
Demand for Robusta coffee is increasing every year, but this situation is not matched with the amount of its availability. This raises problems, especially those related to guaranteeing continuity of coffee quality, limited supply availability, and timeliness of sales. Therefore, this study aims to identify the structure of the Robusta coffee supply chain and analyze the efficiency of the Robusta coffee supply chain performance in Kubu Raya Regency. The method used to identify the structure of the supply chain is descriptive analysis, while the DEA method is used to analyze the efficiency of the members performance of the supply chain. The results indicate that the structure of the supply chain consists of farmers, collectors, wholesalers, and retailers. Overall, the results of the performance efficiency measurement show that the performance of the Robusta coffee supply chain is efficient. However, there are still 4 farmers and 1 trader with inefficient performance, namely DMU1,2,6, and 7 at the farmer level, while at the trader level it is in DMU 5. Therefore, improvements are needed to improve the performance of the supply chain actors by reducing the variable input and increasing the output variable